2017
DOI: 10.17116/terarkh2017891135-43
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of Ixodes tick-borne borreliosis caused by Borrelia miyamotoi in the context of an immune response to the pathogen

Abstract: ITBB-BM is a moderate systemic disease accompanied by the production of specific antibodies in virtually all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Interestingly, only ten of these patients were reactive in an immunoblot test commonly used in two-tier testing for Lyme disease (Table S1). These ten patients did not have erythema migrans or other Lyme borreliosis symptoms, but had a clinical presentation consistent with BMD with fever, thrombocytopenia and lymphopenia [1,22,23]. Since up to 40% of Ixodes ticks are infected with B. burgdorferi sl in the geographical location were these sera were collected, (asymptomatic) concurrent or previous B. burgdorferi sl could explain these positive blot results.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, only ten of these patients were reactive in an immunoblot test commonly used in two-tier testing for Lyme disease (Table S1). These ten patients did not have erythema migrans or other Lyme borreliosis symptoms, but had a clinical presentation consistent with BMD with fever, thrombocytopenia and lymphopenia [1,22,23]. Since up to 40% of Ixodes ticks are infected with B. burgdorferi sl in the geographical location were these sera were collected, (asymptomatic) concurrent or previous B. burgdorferi sl could explain these positive blot results.…”
Section: Discussionmentioning
confidence: 91%
“…Stored sera were used from 46 patients with PCR-confirmed B. miyamotoi infection from two locations, Izhevsk (European Russia) and Yekaterinburg (Asian Russia) [1,22,23]. A total of 191 sera drawn at different time points were available from these 46 patients were tested by C6 Lyme enzyme immunoassay (EIA) (Immunetics, Oxford, UK) according to the manufacturer's instructions.…”
Section: C6 Eia and B Burgdorferi Western Blot In Pcr-proven Bmd Casesmentioning
confidence: 99%
“…In that study, 46 cases of B. miyamotoi disease (BMD) were described with clinical manifestations that included fever and an influenza-like illness, with myalgia and arthralgia amongst other symptoms. Since then, several hundred BMD cases were identified in Russia [34,35]. BMD cases have been reported in Europe and the USA as well, but not with such frequency [2,[36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Both in the USA and in Europe, it has been reported that Borrelia miyamotoi disease in people causes fever (up to 40°C), pain and dizziness, chills, sweating, nausea, vomiting, increased thirst and muscle and joints pains. [5,6,13,14,15].…”
Section: Introductionmentioning
confidence: 99%